503 Role of three dimensional echocardiography and magnetic resonance imaging findings in the decision making and surgical planning of myxomas: correlation with clinical, surgical, and pathological features. (8th December 2021) - Galzerano, Domenico; Alhamshari, Ahmad; Vriz, Olga; Al Admawi, Mohammed; Mirabelli, Francesca; Tashkandi, Loay; Yazzam, Yara; Di Michele, Sara; Khaliel, Feras; Mohammed, Shamayel; Pergola, Valeria; Di Salvo, Giovanni
Abstract: Aims: Transthoracic (TTE), transesophageal echocardiography (TEE), and cardiac Magnetic Resonance Imaging (MRI) are usually the mainstay for diagnosis of cardiac myxomas (MYX). It has been reported that three dimensional (3D) TEE has an additional value in describing the anatomical features. MYX are classified in two types: solid (with a round shape and a non-mobile surface) and papillary (asymmetrical shape with an irregular surface). Even though embolic events are linked to thrombus formation in both types, the latter are more frequently source of embolism. The detection of the attachment of the peduncle and a detailed assessment of the echotexture and of the surface characteristics of the tumour is not always possible by 2D TTE and TEE, therefore MRI is considered the gold standard for diagnosing cardiac tumours and myxomas. Our study aim to determine the accuracy of 3D echocardiographic techniques in the detection of the following anatomical features of the MYX: site of attachment (mid atrial septum, other locations), modality of attachment (pedunculated or sessile), echotexture, surface characteristics in comparison with MRI, and histological findings. Methods and results: We retrospectively reviewed 11 cases of the confirmed myxomas by histology that underwent 2D, 3D TEE, and MRI (6 cases) in the past 6 years in order to assess the ability of the imaging techniques in identifying the anatomical features. Pathology samples were analysed in all patients. Differences in parameters were collected. Our study group is comprised by 10 patients (one recurrence), 8 female, mean age 45.6 ± 14.6 years with 15 myxomas; 11 located in the left atrium [one in left atrial appendage (LAA), one on the mitral valve annulus, 9 near the fossa ovalis], 3 in the right atrium, and 1 on the left ventricular outflow tract (LVOT). Seven were pedunculated, 8 sessile. 2D TEE was not able to diagnose two myxomas. There was an agreement between 2D TEE and 3D TEE in detecting the peduncle except in three patients (only seen by 3D TEE): in the first patient the peduncle was in the atrial septum close to the opening of the left upper pulmonary vein; in the second it was close to the LAA and in the last it was in the LVOT. 3D TEE echotexture analysis matched the pathology in all cases, also in one case of solid tumour with fimbriated edges on a one side which was found to have a clot formation at surgery. There was an excellent matching between the 3D TEE and the MRI in all cases. In our cohort 3DE was able to detect all the morphologic features of the MYX including the site and the type of attachment, the echotexture, and the surface characteristics. The above results led to predict the histologic type, solid, or papillary and there was a correlation with embolism (three patients) and papillary tumours (two patients). Conclusions: 3D TEE and MRI are reliable in assessing the anatomical features of myxomas. The described additional features (peduncle, echotexture, and surface characteristics) seen by these two methods could predict the histological type and have an additional value in the work up of the myxomas leading to correct diagnosis and evaluation of possible complications such as embolic risk. This is helpful to suggest in the management (antiplatelet vs. anticoagulation) and has a pivotal role in programming surgery.